Challenges and Perspectives for Therapeutic Targeting of Myeloproliferative Neoplasms - Sime Brkic; Sara C. Meyer (HemaSphere, 2021)
Myeloproliferative neoplasms (MPNs) are hematopoietic stem cell disorders with dysregulated myeloid blood cell production and propensity for transformation to acute myeloid leukemia, thrombosis, and bleeding. Acquired mutations in JAK2, MPL, and CALR converge on hyperactivation of Janus kinase 2 (JAK2) signaling as a central feature of MPN. Accordingly, JAK2 inhibitors have held promise for therapeutic targeting. After the JAK1/2 inhibitor ruxolitinib, similar JAK2 inhibitors as fedratinib are entering clinical use. While patients benefit with reduced splenomegaly and symptoms, disease-modifying effects on MPN clone size and clonal evolution are modest. Importantly, response to ruxolitinib may be lost upon treatment suggesting the MPN clone acquires resistance. Resistance mutations, as seen with other tyrosine kinase inhibitors, have not been described in MPN patients suggesting that functional processes reactivate JAK2 signaling. Compensatory signaling, which bypasses JAK2 inhibition, and other processes contribute to intrinsic resistance of MPN cells restricting efficacy of JAK2 inhibition overall. Combinations of JAK2 inhibition with pegylated interferon-α, a well-established therapy of MPN, B-cell lymphoma 2 inhibition, and others are in clinical development with the potential to enhance therapeutic efficacy. Novel single-agent approaches targeting other molecules than JAK2 are being investigated clinically. Special focus should be placed on myelofibrosis patients with anemia and thrombocytopenia, a delicate patient population at high need for options. The extending range of new treatment approaches will increase the therapeutic options for MPN patients. This calls for concomitant improvement of our insight into MPN biology to inform tailored therapeutic strategies for individual MPN patients.